2004
DOI: 10.1021/bi0492657
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Type 1 Cu Sites ofHyphomicrobium denitrificansNitrite Reductase:  A New Class of Copper-Containing Nitrite Reductases

Abstract: We report (1) the amino acid sequence of Hyphomicrobium denitrificans nitrite reductase (HdNIR), containing two type 1 Cu sites and one type 2 Cu site; (2) the expression and preparation of wild-type HdNIR and two mutants replacing the Cys ligand of each type 1 Cu with Ala; and (3) their spectroscopic and functional characterization. The open-reading frame of 50-kDa HdNIR is composed of the 15-kDa N-terminal domain having a type 1 Cu-binding motif like cupredoxins and the 35-kDa C-terminal domain having type 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…H. denitrificans is characterized by its unique nitrite re- ductase, which is clearly distinct from the nitrite reductases found in other Hyphomicrobium species. It is characterized by the presence of two type I Cu sites, as opposed to the single type I Cu site found in the nitrite reductases of most bacteria (16,17,45). The role of this second type I Cu site has not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. denitrificans is characterized by its unique nitrite re- ductase, which is clearly distinct from the nitrite reductases found in other Hyphomicrobium species. It is characterized by the presence of two type I Cu sites, as opposed to the single type I Cu site found in the nitrite reductases of most bacteria (16,17,45). The role of this second type I Cu site has not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…H. denitrificans (5) is commonly found in soils, freshwater environments, and activated sludge. This bacterium has the capacity to denitrify (2), and its nitrite and nitrous oxide reductases were previously characterized (15)(16)(17)(18). H. zavarzinii is a soil bacterium that has been studied mainly for the biotechnological potential of the exceptional formaldehyde dehydrogenase found in strain ZV580 (19,20).…”
mentioning
confidence: 99%
“…PCR amplicons were cleaned as described above and sequenced directly. Primers specific to the nirK gene of Hyphomicrobium denitrificans were designed using a previously published sequence of H. denitrificans strain A3151 (primer set 4 [64]). A primer set for this gene was generated using the online software Primer-BLAST at the NCBI website (51).…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid sequence of the C-terminal region shows a significant similarity (48% identity) to that of class II CuNIR AniA from Neisseria gonorrhoeae (10). Moreover, according to the mutation of HdNIR, C114A and C260A possessing one type 1 Cu and one type 2 Cu demonstrated that the N-terminal and C-terminal regions have blue and green type 1 Cu sites, respectively (13,14). Here we describe the crystal structure of HdNIR at a resolution of 2.2 Å and the functions of the Cu centers.…”
mentioning
confidence: 89%